2012
DOI: 10.1590/s1516-18462012005000020
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre o tempo e o tipo de amamentação e as funções do sistema estomatognático

Abstract: OBJETIVO: investigar a relação do tempo e tipo de aleitamento com as funções de mastigação, deglutição e respiração. MÉTODO: a amostra foi constituída por 52 crianças de ambos os sexos, na faixa etária de 5 a 8 anos. Utilizando-se de questionário, foram coletados dados referentes ao tipo e tempo de amamentação e respiração das crianças. As mesmas foram submetidas à avaliação clínica das funções, a qual baseou-se no Protocolo de Avaliação Miofuncional Orofacial com Escores Expandido (AMIOFE- E). Os dados foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
1
4
0
10
Order By: Relevance
“…Considering the relationship between mastication and aspects related to diet, a study performed with 144 children from three to five years old investigated the association between breastfeeding and quality of mastication function. The findings showed positive correlation among such variables, agreeing with another research 30 , however, in the present study, it was not observed such association. In this study, the children who were breastfed for at least 12 months presented mastication mean scores significantly higher, similarly to another study 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Considering the relationship between mastication and aspects related to diet, a study performed with 144 children from three to five years old investigated the association between breastfeeding and quality of mastication function. The findings showed positive correlation among such variables, agreeing with another research 30 , however, in the present study, it was not observed such association. In this study, the children who were breastfed for at least 12 months presented mastication mean scores significantly higher, similarly to another study 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Neste estudo, ter "dificuldade ou demora de engolir os alimentos" e "queixa de obstrução nasal esporadicamente" foi associado ao tempo de amamentação. Este resultado diverge do encontrado em um estudo realizado com 52 crianças de ambos os sexos, de cinco a oito anos, no qual o tempo e tipo de aleitamento não foram associados estatisticamente com as funções de mastigação, deglutição e respiração 19 . Lopes et al 17 não encontraram associações com significância estatística entre a duração da amamentação exclusiva ou total com os padrões de respiração em crianças com média de três anos.…”
Section: Resultsunclassified
“…The behavior of this indicator was rather heterogeneous, ranging from 27.1% in Cuiabá/MT to 56.1% in Belém/ PA 13 . In one study it was verified that the prevalent type of feeding was mixed, because 61.54% of the 141 children were breastfed and bottle fed, and as regards the time of natural breastfeeding, it was observed that the majority (40.38% of the children) were not breastfed or received it for a short time 14 .…”
Section: Discussionmentioning
confidence: 99%